Perubahan, Kontinuitas, Struktur Musik, Dan Teks Realisasi Nyanyian Buku Ende dan Kidung Jemaat Yamuger - Muhammad Yusuf (Gondang: Jurnal Seni dan Budaya, 2017)
This study used qualitative methods with participant observer to study Continuity and change of Ende Book and Yamuger's Song of the Church is an integral part of church music. Continuity and change by using synchronic and historical diachronic theory. To study the structure of music used the theory of weighted scale, rhythm, and the relationship of music with text. To study the text used semiotic theory. The origins of song and melody texts are from the German Protestant congregation, which is then translated into Batak (Ende's Book) and Indonesian (Yamunger's Song of the Church). On the other hand, there are also direct translations that give rise to differences of etymological and semantic meaning between these three types of chanting. In the context of sosioreligious, Batak language has been very fulfilled into a language of religious choice in worship, to strengthen the social sentiments that cause the emergence of religious emotions and the attainment of the inner atmosphere of the congregation. Among young people the phenomenon above is true, but not in all places or locations of the support community, so the doubt about its loyalty to Ende's Book is undoubtedly not a latent danger. Social sentiment that causes the emergence of religious emotion is still considered strong, but it is expected that there will be a system that will be a benchmark to be able to stay awake.